A case series evaluating microwave-based therapy for axillary hyperhidrosis and bromhidrosis. (3rd April 2022) - Mohamoud, Abdiweli Awil; Zeraiq, Lina; Vestergaard, Tine
Abstract: Introduction: Axillary hyperhidrosis and bromhidrosis have serious social, emotional, and professional consequences. There are several treatments of axillary hyperhidrosis. We present a case series evaluating the efficacy and safety of microwave device for axillary hyperhidrosis and bromhidrosis. Materials and methods: Seven patients were included in our case series. Four patients had both hyperhidrosis and bromhidrosis. Three patients had only hyperhidrosis. To evaluate the degree of hyperhidrosis and degree bromhidrosis a self-reported Hyperhidrosis Disease Severity Scale (HDSS) score and 4-point malodor grade were assessed. All patients underwent 1 or 2 microwave treatments. Patients underwent a survey on treatment outcomes and adverse effect conducted through telephone 12 months after their last procedure. Results: Six of seven patients had a 2-point drop in HDSS score. The four patients with bromhidrosis had a 2-point drop on the self-reported malodor measurement 12 months post treatment. Minor adverse effects related to the therapy occurred. Conclusion: This novel microwave-based treatment was effective for the treatment of axillary hyperhidrosis and bromhidrosis. Patient satisfaction with the procedure is high, and adverse events are typically transient and well tolerated.